2021
DOI: 10.3390/ijerph18105076
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bio-Risk Management System Implementation in Indonesian Higher Education Laboratory

Abstract: Developing countries face various challenges in implementing bio-risk management systems in the laboratory. In addition, educational settings are considered as workplaces with biohazard risks. Every activity in a laboratory facility carries many potential hazards that can impact human health and the environment and may cause laboratory incidents, including Laboratory Acquired Infections (LAIs). In an effort to minimize the impact and occurrence of these incidents, it is necessary to evaluate the implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Similar approaches using a scoring tool or checklist to assess laboratory systems or reference laboratories have been successfully used in sub-Saharan African countries, 23 including Ghana, 24 as well as Indonesia, 25 Malaysia, 26 and Thailand. 27 In Burkina Faso, strengthening human resource capacity at the Directorate of Laboratory—focusing on use of the biosafety and biosecurity assessment tool—enabled the country to accurately monitor the implementation of recommendations and the roadmap, which were developed at the end of the training.…”
Section: Discussionmentioning
confidence: 99%
“…Similar approaches using a scoring tool or checklist to assess laboratory systems or reference laboratories have been successfully used in sub-Saharan African countries, 23 including Ghana, 24 as well as Indonesia, 25 Malaysia, 26 and Thailand. 27 In Burkina Faso, strengthening human resource capacity at the Directorate of Laboratory—focusing on use of the biosafety and biosecurity assessment tool—enabled the country to accurately monitor the implementation of recommendations and the roadmap, which were developed at the end of the training.…”
Section: Discussionmentioning
confidence: 99%
“…Talbot et al (2014) stressed the importance of external Quality Assurance Agency, which conducts full institutional evaluations every five years in all UK universities to adopt a risk-based strategy to regulate the universities. Besides, many researchers found that ISO 31000 is the standard commonly used to implement RM (Hassen and Zakaria, 2013; Priyarsono et al , 2019; Bowolaksono et al , 2021). The internal audit department then serves a critical governance and RM role in overseeing and monitoring the RM processes (Soobaroyen et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
“…IS RM identifies and reduces IS threats, include aspects of confidentiality, reliability and accessibility, through the identification of assets, weaknesses and risks, followed by the identification of the impact, possibility and risk value (Johan et al , 2019). bio-RM incorporates a risk assessment of all risks, including laboratory operations, duties and obligations of staff in laboratories and roles held by the top levels of management (Bowolaksono et al , 2021). Participatory RM highlights safety of individuals in outdoor activities (Beery, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite advances in technology, the availability of more sophisticated instruments for laboratory use, and the availability of personal protective equipment, human error remains one of the most inherent factors at the origin of accidents ( 7 ). Inadvertent exposures to infectious agents in the laboratory, and associated laboratory-acquired infections, are more common in low and middle-income countries ( 8 , 9 ). According to the WHO, dual-use research of concern (DURC) constitutes research that may be legitimately conducted for biomedical or other benefits, but which might also be misapplied to do harm.…”
Section: Introductionmentioning
confidence: 99%